An association between decreasing incidence of invasive non-typhoidal salmonellosis and increased use of antiretroviral therapy, Gauteng Province, South Africa, 2003–2013 - Keddy, Karen H. (PLoS One, 2017)
BACKGROUND: HIV-infected persons are at increased risk of opportunistic infections, including invasive nontyphoidal Salmonella (iNTS) infections; antiretroviral therapy (ART) reduces this risk. We explored changing iNTS incidence associated with increasing ART availability in South Africa. METHODS: Laboratory-based surveillance for iNTS was conducted in Gauteng Province, South Africa, with verification using the National Health Laboratory Service’s Central Data Warehouse (CDW), between 2003 and 2013. Isolates were serotyped at the Centre for Enteric Diseases. CDW data on patient numbers obtaining HIV viral load measurements provided estimates of numbers of HIV-infected patients receiving ART. A Poisson regression model was used to measure the changing incidence of iNTS infection from 2003 to 2013. The correlation between the incidence of iNTS and ART use from 2004 to 2013 was determined using Pearson’s correlation coefficient. RESULTS: From 2003–2013, the incidence of iNTS per 100,000 population per year decreased from 5.0 to 2.2 (p < .001). From 2004 to 2013, the incidence per 100,000 population of HIV viral load testing increased from 75.2 to 3,620.3 (p < .001). The most common serotypes causing invasive disease were Salmonella enterica serovar Typhimurium (Salmonella Typhimurium), and Salmonella Enteritidis: 2,469 (55.4%) and 1,156 (25.9%) of 4,459 isolates serotyped, respectively. A strong negative correlation was observed between decreasing iNTS incidence and increasing ART use from 2004 to 2013 (r = -0.94, p < .001). Similarly, decreasing incidence of invasive Salmonella Typhimurium infection correlated with increasing ART use (r = -0.93, p < .001). Incidence of invasive Salmonella Enteritidis infection increased, however (r = 0.95, p < .001). Between 2003 and 2004, fewer adult men than women presented with iNTS (male-to-female rate ratio 0.73 and 0.89, respectively). This was reversed from 2005 through 2013 (ranging from 1.07 in 2005 to 1.44 in 2013). Adult men accessed ART less (male-to-female rate ratio ranging from 0.61 [2004] to 0.67 [2013]). CONCLUSIONS: The incidence of iNTS infections including Salmonella Typhimurium decreased significantly in Gauteng Province in association with increased ART utilization. Adult men accessed ART programs less than women, translating into increasing iNTS incidence in this group. Monitoring iNTS incidence may assist in monitoring the ART program. Increasing incidence of invasive Salmonella Enteritidis infections needs further elucidation.